Dynamical diagnostics of the edges of the polar vortices - Rummukainen, M.; Knudsen, B.; von der Gathen, Peter (1994)
The dynamically induced stratospheric polar vortices are major factors in the formation and evolution of large chemicallyperturbed regions in both hemispheres during respective winter months. For a proper understanding of thephysicochemical processes in the polar stratospheres, it is necessary to be able to keep track of the extents andpositions of the polar vortices. This has often been done with the help of the maximum gradient of Ertel's potential vorticity(PV) on isentropic surfaces, which should bring out the edges of a polar vortex. The approaches have, however, beenmostly qualitative in nature. In this work, we define the edges of the polar vortices during one Antarctic and two Arcticwinters an two stratospheric levels with the help of ECMWF global initialized analysis fields. Our definition of a polar vortexis based on isentropic total wind maxima at successive 1.5 degrees longitude bins encircling the respective pole. Aretrieval of the isentropic PV values along the diagnosed vortex edges permits us to subsequently perform a quantitativecomparison between vortex edge defined by the total wind maxima, and the variability of isentropic PV values there. Itappears that one is able to assign discrete ranges of PV for diagnosing the edges of the polar vortices. However, suchranges exhibit variability on time scales longer than a few months, as well as between individual winters. This should betaken into account when using PV in the interpretation of experimental data.